The anticancer, antioxidant and phytochemical screening of Philenoptera violacea and Xanthocercis zambesiaca leaf, flower & twig extracts - Ntsoelinyane, P. H.; Mashele, S. S.; Manduna, I. T. (International Journal of Pharmacological Research, 2014)
The aim of this study was to investigate the antioxidant potential, anticancer activity, phytochemical constituents and total phenolic content of Philenoptera violacea and Xanthocercis zambesiaca leaves, flower & twig extracts. The anticancer activity of the extracts was tested in the 5-cell line panel consisting of MCF7 (breast cancer), HCT116 (colon cancer), TK10 (renal), UACC62 (melanoma) and PC3 (prostate cancer) by Sulforhodamine B (SRB) assay at the CSIR. The scavenging activities of the Xanthocercis zambesiaca extract and Philenoptera violacea was determined by 2, 2- diphenyl-1-picrylhydrazyl (DPPH) assay and was compared with standard antioxidant (ascorbic acid). Xanthocercis zambesiaca showed moderate (50%) free radical scavenging activity, while Philenoptera violacea extract had low free radical scavenging activity at the concentration of 2.5 mg/ml when compared to ascorbic acid. Qualitative phytochemical analysis of these plant extracts confirmed the presence of tannins, flavonoids, steroids, terpenoids, alkaloids and cardiac glycosides from Philenoptera violacea extract, while Xanthocercis zambesiaca extract showed the presence of flavonoids, saponnins, terpenoids and glycosides. Both extracts showed inactivity against all 5 cell lines with an IC50 of more than 100 μg/ml. Our results indicate that, Xanthocercis zambesiaca extract is a weak source of antioxidant and Philenoptera violacea extract has a number of phytochemical compounds. Future study will be done to isolate and identify the active compounds of both these plants.
Published Article
Keywords: Philenoptera violacea; Xanthocercis zambesiaca; Anticancer activity; Phytochemical constituents; Antioxidant activity